Differences between potassium and sodium incorporation in foraminiferal shell carbonate - Pacho, Laura; De Nooijer, Lennart Jan; Boer, Wim; Reichart, Gert-Jan (Frontiers in Marine Science, 2024)
The isotopic and elemental composition of the fossil shells of foraminifera are often used for reconstructing past environments and climates. These so-called proxy relations are based on the effect of environmental conditions (e.g. seawater temperature, pH) on the isotopic ratio (e.g. δ11B or δ18O) or partitioning of elements (commonly expressed as El/Ca or DEl) during calcification. Whereas many studies focused on proxy-calibrations of divalent cations, incorporation of monovalent cations are less well constrained. Here we calibrate shell potassium content (K/Cacc) as a function of 1) seawater K+ concentration, 2) the ratio of potassium and calcium in seawater (K/Casw) and 3) temperature. Moreover, we analyze Na+ incorporation into the calcite as a function of seawater K+ and Ca2+ concentrations. First, we cultured specimens of the larger benthic foraminifer Amphistegina lessonii at four different seawater [Ca2+] and constant [K+], resulting in a range of K/Casw. Secondly, we cultured specimens of the same species at four different [Ca2+]sw and [K+]sw while keeping the ratio between these two ions constant. Finally, we tested the effect of temperature (from 18 to 28°C) on K-incorporation in this species. Measured K/Cacc values are not notably affected by [Ca2+]sw, while seawater [K+] positively influences potassium incorporation, resulting in a positive correlation between seawater K/Ca values and K/Cacc. Although the [Na+] in the culture media was constant throughout both experiments, incorporated Na responded positively to decreasing [Ca2+]sw, resulting in a positive correlation between sea water Na/Ca and Na/Cacc. The difference in the controls on K- and Na-incorporation suggests that the (biological) control on these ions differs. Part of the observed variability in element partitioning may be explained by differences in chemical speciation and crystallographic coordination in the calcite lattice.